(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
This research investigates the potential of using crushed glass and waste bottle plastic fibers as sustainable additives to enhance the performance of concrete in terms of strength and flexural properties. The study involves incorporating varying percentages of crushed glass (CG) and waste bottle plastic fibers (PE) fibers into concrete mixtures and assessing the changes in compressive and flexural strength across different curing periods, namely 7, 28, 56, and 90 days. The results reveal that the optimal combination for improved performance is 15% CG and 10% PE fibers, as it consistently demonstrates the highest percentage improvement in both compressive and flexural strength across all curing periods. The findings of this study have significant implications for sustainable construction practices, as incorporating crushed glass and waste bottle plastic fibers in concrete mixtures not only improves the material's performance but also promotes recycling and repurposing waste materials. Furthermore, the use of these recycled materials could lead to cost savings, reduced material volume, lower labor costs, and improved abrasion resistance in construction projects.